2021
DOI: 10.21203/rs.3.rs-379158/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ITGA2, LAMB3, and LAMC2 May Be the Potential Therapeutic Targets in Pancreatic Ductal Adenocarcinoma: an Integrated Bioinformatics Analysis

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the most common form of pancreatic cancer with an abysmal prognosis rate over the last few decades. Early diagnosis and prevention could effectively combat this malignancy. Therefore, it is crucial to discover potential biomarkers to identify asymptomatic premalignant or early malignant tumors of PDAC. Gene expression analysis is a powerful technique to identify candidate biomarkers involved in disease progression. In the present study, five independent gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Furthermore, laminins LAMBC2 and LAMB3 support cancer progression and resistance to gemcitabine -one of the main chemotherapeutics used in PDAC patients [61,62]. In general, the association with poor prognosis of the stroma signature is consistent with the one described in previous studies for each gene: CEACAM5 [63], CEACAM6 [64], FN1 [65], GJB2 [66], GPRC5A [67], LAMB3 [68,69], LAMC2 [68,69], SFN [70], SLC6A14 [71], TSPAN1 [72], VCAN [65]. The meta-analysis from transcriptomic studies allows a be er understanding of the PDAC environment.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, laminins LAMBC2 and LAMB3 support cancer progression and resistance to gemcitabine -one of the main chemotherapeutics used in PDAC patients [61,62]. In general, the association with poor prognosis of the stroma signature is consistent with the one described in previous studies for each gene: CEACAM5 [63], CEACAM6 [64], FN1 [65], GJB2 [66], GPRC5A [67], LAMB3 [68,69], LAMC2 [68,69], SFN [70], SLC6A14 [71], TSPAN1 [72], VCAN [65]. The meta-analysis from transcriptomic studies allows a be er understanding of the PDAC environment.…”
Section: Discussionsupporting
confidence: 86%
“…Laminin γ2 is a subunit of glycoprotein laminin 322 that forms a web-like structure, providing tensile strength to the basement membrane in ECM [45]. Laminin γ2 is identified as a metastatic marker with high expression in a number of cancers [45], including LUAD [23] and pancreatic ductal adenocarcinoma [46] because it enhances metastatic potential through integrin β1, ZEB1, and SNAI1-mediated EMT [23]. In addition, TSG6 is involved in ECM stability during EMT and cell migration as an HA binding protein, a main component of proteoglycans in the ECM, which is a central factor for the EMT of renal tubular epithelial cells in a CD44-dependent manner [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al identified common driver genes for T2D and cardiovascular disease from genome-wide association studies within women from different ethnicities [12]. Other studies have also aimed to contribute to the understanding of molecular mechanism of pancreas-related disorders and provide therapeutic targets [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Chan et al identified common driver genes for T2D and cardiovascular disease from genome-wide association studies within women of different ethnicities [12]. Other studies have also contributed to the understanding of molecular mechanism of pancreas-related disorders and provide therapeutic targets [13][14][15][16][17]. Several computational methods have been developed for the identification of significant differentially expressed genes as inputs for enrichment analysis tools (e.g., Enrichr) to evaluate biological functions.…”
Section: Introductionmentioning
confidence: 99%